(untitled) - Maxwell, Sarah (Hoboken, N.J., 2008)
Pricing--and the questions around what consumers pay for almost anything--have become commonplace. Think about the Sprint commercial featuring children being given rules about how they can play--as a way for Sprint to show how mobile phone pricing can be unfair. Likewise, there are ads discussing the different costs passengers are paying for seats on the same airline flights. Some consumers in the US have turned to Canada to buy lower cost drugs. This book will show how pricing can arouse a variety of reactions among consumers and how the notion of "fair" has a different meaning to different consumers. The author explains that price is "the medium between what we have and what we want… we want to pay only what a thing is worth." The book will explain what makes a price seem wrong, what are the social norms of a fair pricing and cultural differences.
Keywords: Prices,Pricing,Giá cả,Vật giá